2016
DOI: 10.7554/elife.21337
|View full text |Cite
|
Sign up to set email alerts
|

Spatial patterning of P granules by RNA-induced phase separation of the intrinsically-disordered protein MEG-3

Abstract: RNA granules are non-membrane bound cellular compartments that contain RNA and RNA binding proteins. The molecular mechanisms that regulate the spatial distribution of RNA granules in cells are poorly understood. During polarization of the C. elegans zygote, germline RNA granules, called P granules, assemble preferentially in the posterior cytoplasm. We present evidence that P granule asymmetry depends on RNA-induced phase separation of the granule scaffold MEG-3. MEG-3 is an intrinsically disordered protein t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
264
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(269 citation statements)
references
References 37 publications
5
264
0
Order By: Relevance
“…In pptr-1 mutants, P granules are evenly distributed throughout the embryo, and are reduced drastically in number and size 37,38 . PPTR-1 acts on MEG-3 and MEG-4, which are intrinsically-disordered serine-rich proteins that function redundantly to stabilize the condensed phase of P granules via binding of RNA and PGL-1 39,40 . In comparison to wild type animals, meg-3/4 zygotes display a ~90% loss of P granules 39 .…”
Section: Introductionmentioning
confidence: 99%
“…In pptr-1 mutants, P granules are evenly distributed throughout the embryo, and are reduced drastically in number and size 37,38 . PPTR-1 acts on MEG-3 and MEG-4, which are intrinsically-disordered serine-rich proteins that function redundantly to stabilize the condensed phase of P granules via binding of RNA and PGL-1 39,40 . In comparison to wild type animals, meg-3/4 zygotes display a ~90% loss of P granules 39 .…”
Section: Introductionmentioning
confidence: 99%
“…Multivalent interactions in PFK-1.1 mediate its condensation. Liquid-liquid phase separation can be induced via multivalent protein-protein and protein-RNA interactions (Alberti et al, 2019;Banani et al, 2017;Elbaum-Garfinkle et al, 2015;Langdon et al, 2018;Li et al, 2012;Nott et al, 2015;Smith et al, 2016;Wang et al, 2018;Zhang et al, 2015). PFK exists as a homotetramer capable of self-associating into higher-order structures (Webb et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Multivalent interactions between proteins, or proteins and RNAs, play important roles in driving condensates into liquid-like protein droplets (Banani et al, 2017). Multivalent interactions can be mediated via folded protein domains, or intrinsically disordered regions (IDRs) with multiple interacting motifs (Alberti et al, 2019;Elbaum-Garfinkle et al, 2015;Langdon et al, 2018;Li et al, 2012;Nott et al, 2015;Smith et al, 2016;Wang et al, 2018;Zhang et al, 2015). These interactions leading to phase separation can be recapitulated in vivo and in vitro by engineering self-association domains (Bracha et al, 2018;Li et al, 2012;, underscoring the importance (and sufficiency) of multivalent interactions in the formation of condensates.…”
Section: Multivalent Interactions Underlie Pfk-11 Condensate Formationmentioning
confidence: 99%
“…This process is repeated during further cell divisions, such that the P granules continue to segregate into those cells that will eventually give rise to the germ cells. Now, in eLife, Geraldine Seydoux and colleagues at the Johns Hopkins University School of Medicine – including Jarrett Smith as first author – report how two RNA-binding proteins with opposing effects control where P granules form (Smith et al, 2016). …”
mentioning
confidence: 99%
“…MEX-5 and MEG-3 bind to RNA with little specificity (Pagano et al, 2007; Smith et al, 2016), but the adaptor proteins found in germ cells might make it possible for these proteins to bind to different sets of mRNAs (Weidmann et al, 2016). This selective binding could establish a gradient of specific mRNAs that runs from the front to the back of the zygote, with critical mRNAs being captured at the end of the cell that goes on to become the germ cells (Gallo et al, 2010; Lehmann, 2016; Seydoux and Braun, 2006).…”
mentioning
confidence: 99%